Undifferentiated pleomorphic sarcoma in the anterior mediastinum with a rapidly progressive course: A case report - Sato, Masamichi (EXCLI J, 2020)
A 77-year-old woman with heart failure was admitted to our hospital. Computed tomography (CT) of the chest revealed an anterior mediastinal tumor. CT-guided biopsy revealed a malignant nonepithelial tumor of unknown origin. She was not treated with chemotherapy or radiotherapy because of her poor clinical condition. She died 33 days after admission. Following autopsy, we confirmed that the mediastinal tumor had infiltrated the large blood vessels. After final histological examination, undifferentiated pleomorphic sarcoma was diagnosed. Primary mediastinal sarcomas are very rare; clinicians should be aware of their possibility because some cases may progress rapidly as evidenced in this case.